Cross-cultural evidence that shame is a defense against reputational damage - Yiftach Argaman; Daniel Sznycer; Jan Crusius; Florian van Leeuwen; Yohsuke Ohtsubo; Hitomi Ishihara; Jin-Ying Zhuang; Qi-Jun Zhou; Thomas Castelain; Félix Neto; Joana Neto; Assaf Kron (Proceedings of the National Academy of Sciences, 2026)
Because shame leads to evasions, aggression, and other behaviors that victims and third parties find undesirable, a prominent theory regards this emotion as maladaptive. By contrast, an alternative, adaptationist theory asks whether shame might benefit the actor. Indications that an individual now offers fewer benefits or imposes greater costs on others, if they reach others’ minds, lead the individual to be socially devalued: Others become less inclined to help and more inclined to harm her. Thus, an adaptationist theory views shame as a neurocognitive adaptation designed to minimize the leakage of reputation-damaging information and the cost of being devalued. Here, we report tests of two predictions derived from the adaptationist theory across six countries—the United States, the Netherlands, Portugal, Spain, Japan, and China—and two cultural regions within the United States—Southern states (honor) and Northern states (nonhonor). First, failures that indicate reductions in abilities more highly valued by others will elicit more intense shame. Second, failures will trigger greater shame when they occur in public rather than in private. The data supported both predictions in all six countries and in both US cultural regions. The improbable fit between the severity of the devaluative threat and the intensity of shame suggests that this emotion is an adaptation. Further, the replication of these findings across regions that vary widely along the individualism–collectivism and honor–nonhonor dimensions suggests that shame is part of human nature rather than a cultural construction.